2017
DOI: 10.1080/15384101.2017.1295193
|View full text |Cite
|
Sign up to set email alerts
|

Prohibitin promotes androgen receptor activation in ER-positive breast cancer

Abstract: Prohibitin (PHB) is an evolutionarily conserved protein with multiple functions in both normal and cancer cells. Androgen receptor (AR) was reported to act as a different role in the ER-positive and ER-negative breast cancer. However, little is known about the role of PHB and whether PHB could regulate AR expression in the ER-positive breast cancer. Here, we determined the expression and clinical outcomes of PHB in breast cancer samples using 121 breast cancer tissues and published databases, and investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 31 publications
1
10
0
1
Order By: Relevance
“…Upon BRCA1 interference, we found a reduced level of prohibitin, coherently with literature data that highlighted the ability of prohibitin in inhibiting breast cancer cell proliferation and promoting apoptosis [33]. In addition, we found a reduced level of gelsolin, fully in agreement with what we previously published [20].…”
Section: Discussionsupporting
confidence: 92%
“…Upon BRCA1 interference, we found a reduced level of prohibitin, coherently with literature data that highlighted the ability of prohibitin in inhibiting breast cancer cell proliferation and promoting apoptosis [33]. In addition, we found a reduced level of gelsolin, fully in agreement with what we previously published [20].…”
Section: Discussionsupporting
confidence: 92%
“…Since the original identification of PHB1 as a proliferation suppressor in rat liver cells 1 , the effect of PHB1 on cancer proliferation has been studied. Some studies found that PHB1 inhibits breast cancer cell proliferation by up-regulating androgen receptor (AR) expression in estrogen receptor (ER)-positive breast cancer cells 15 , 63 . PHB1 also inhibits proliferation of human osteosarcoma MG-63 cells by interacting with tumor suppressors such as p53 64 .…”
Section: Role Of Phb1 and Phb2 In Tumorigenesismentioning
confidence: 99%
“…It has been reported that AR is expressed in 60-70% of ER À BC and in approximately 68% of the cases in this research. 26,27 The AR signalling pathway has a significant role in the proliferation and survival of ER À BCs, and inhibition of AR has a therapeutic value in in-vitro and in-vivo models of ER À AR + BC cells. 28 PDEF was first identified as an AR co-regulator and an activator of prostate-specific antigen (PSA) in the prostate.…”
Section: S U R V I V a L A N A L Y S I Smentioning
confidence: 99%